Decreased expression of SEMA4D in recurrent implantation failure induces reduction of trophoblast invasion and migration via the Met/PI3K/Akt pathway. (September 2022) - Chen, Xian; Qi, Lingbin; Zhao, Chenyang; Xue, Jinfeng; Chen, Mingye; Diao, Lianghui; He, Wen; Lv, Bo; Zeng, Yong; Xue, Zhigang
Abstract: Recurrent implantation failure (RIF) associated with impaired endometrial receptivity and other factors. Disease-specific therapy has yet to be developed due to the lack of understanding of underlying mechanism(s). Herein we investigated the key factors of endometrial receptivity in RIF patients by transcriptomic sequencing. In vitro cellular model was used to delineate the molecular mechanism of key factors on proliferation, invasion and migration of trophoblast cells. SEMA4D was identified as the key factors of endometrial receptivity with significantly lower expression in the mid-secretory endometrium of RIF patients compared with those from normal fertile women. The binding of SEMA4D to its receptor Plexin-B1 on human trophoblast cells HTR-8/SVneo resulted in the activation of Met/PI3K/Akt signaling, which promotes trophoblast cell invasion and migration by enhancing MMP-2 expression. Moreover, the effect of SEMA4D on HTR-8/SVneo could be blocked by knocking down Met with specific siRNA or treating with LY294002. Collectively, our data indicate that decreased expression of SEMA4D in endometrium impair the process of trophoblast invasion and migration through Met/PI3K/Akt pathway, which provides insights into this essential physiological process in the development of RIF. Highlights: SEMA4D is a potential novel factor of the mid-luteal endometrium in the RIF patients. SEMA4D promoted HTR-8/SVneo cells invasion and migration via Met/PI3K/Akt pathway. SEMA4D promoted MMP-2 expression in HTR-8/SVneo cells. Knockdown of Met could block SEMA4D mediated effects on trophoblast behavior. Inhibition of the PI3K/Akt pathway abrogated SEMA4D mediated effects on trophoblast behavior.